Knowledge, attitude, and practices towards COVID-19 among ayurvedic practitioners of Karnataka, India: a cross-sectional survey - Khanum, Rufia Shaistha; ., Amoghashree; Kumar, D. Sunil; Verma, Satendra Kumar; N., Chandan; Narayanmurthy, M. R. (International Journal Of Community Medicine And Public Health, 2020)
Background: COVID-19 is a highly infectious disease which was first identified in Wuhan, China and was subsequently declared as pandemic by WHO. As it is rapidly spreading and taken lives of millions, various countries have adopted unprecedented measures and treatment modalities. Since India has historical roots of Ayurveda, Ayurvedic system of medicine was consider to boost the immunity and also to prevent the infection. Hence the knowledge, attitude and practice of an Ayurvedic practitioner plays a major role in health system, which further helps to know the preparedness among them. With this context this study was conducted to assess knowledge, attitude and practice among them towards COVID-19. Methods: Online cross sectional study was done among Ayurvedic practitioners of Karnataka. Google form was sent through social media to collect data and analysed using SPSS 25. Results: The mean age among the participants was 30.5±9.1 years. Majority were females (54.3%), and 59.1% are currently practicing Ayurveda. Mean knowledge score was 10.5±1.9, thus 86.6% of the participants had good knowledge. 70.1% agreed for the fact that Ayurveda should be considered as a mainstream medicine whereas 88.2% were in opinion that Ayurveda should be considered as complementary therapy along with conventional treatment. Statistical association was seen between education and knowledge. Conclusions: Good knowledge towards COVID-19 was seen among 86.6% and majority of them want Ayurveda to be considered as complementary medicine but before that evidence based treatment protocol needs to be developed to support claims regarding treatment/prevention of COVID-19.